1993
DOI: 10.1128/jvi.67.6.3191-3198.1993
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid human immunodeficiency virus Gag particles as an antigen carrier system: induction of cytotoxic T-cell and humoral responses by a Gag:V3 fusion

Abstract: In attempts to increase the immunogenicity of recombinant antigens, a number of particulate antigen presentation systems have been developed. In this study, we used human immunodeficiency virus Gag particles as carriers for the human immunodeficiency virus envelope V3 region. Gag:V3 fusion proteins were expressed from baculovirus expression vectors; they migrated to the insect cell membrane and budded from the cells as hybrid particles. An immunization study carried out with rats showed that the particles elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…31 Some protein complexes that physically mimic viral particles have also been found to effectively elicit CTLs against hepatitis B surface antigen 32 that assembles into 20 nm particles and the yeast retrotransposon encoded protein Ty that assembles into virus-like particles (VLP). 33 The filamentous phage particle is an asymmetric particle about 6 nm in diameter and 800 -2,000 nm long, comprising a sheath of several thousand gpVIII around a single-stranded circular DNA molecule at the core. 34 Recently we found that the recombinant filamentous phage particles that displayed CTL epitope from hepatitis B virus surface antigen primed strong MHC class I-restricted CTL responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…31 Some protein complexes that physically mimic viral particles have also been found to effectively elicit CTLs against hepatitis B surface antigen 32 that assembles into 20 nm particles and the yeast retrotransposon encoded protein Ty that assembles into virus-like particles (VLP). 33 The filamentous phage particle is an asymmetric particle about 6 nm in diameter and 800 -2,000 nm long, comprising a sheath of several thousand gpVIII around a single-stranded circular DNA molecule at the core. 34 Recently we found that the recombinant filamentous phage particles that displayed CTL epitope from hepatitis B virus surface antigen primed strong MHC class I-restricted CTL responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus (HBV)-derived particulate core (HBcAg) and surface (HBsAg) antigens have been widely used for analyzing T cell immunity to HBV [1], and the high immunogenicity of these antigens has also led to the consideration of these molecules as carriers for foreign antigens [2,3]. The development of other virus-like particle systems to deliver foreign epitopes or antigens has proven that such non-replicating vectors represent an efficient and completely safe strategy for eliciting T cell immune responses [4][5][6][7]. However, to date only little is known about the mechanism of uptake and the processing requirements of virus-like particles leading to presentation of such antigens to T cells by MHC molecules.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, a variety of modified forms of exogenous antigens have been shown to be processed for MHC class I presentation, indicating the presence of alternative pathways [5]. These different exogenous antigens include whole cells [6,7], inactivated viruses [8], immune stimulating complex [9][10][11][12], liposomes [13][14][15], heat shock protein-bound antigens [16][17], recombinant bacteria [18], antigen-coupled beads [19], lipid conjugated antigens [20], and denatured and/or aggregated proteins [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%